Communicative process in the emergency department between nursing staff and patients: social representations - Zani, Adriana Valongo; Marcon, Sônia Silva; Tonete, Vera Lúcia Pamplona [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP] (GN1 Sistemas e Publicacoes, 2014)
Aim: To describe and analyze the communication process established between nursing professionals (nurses and nursing technicians) and patient/family in the ER, from the perspective of professionals and patients involved. Method: A qualitative approach based on the Theory of Social Representation was used. The sample was formed by 40 subjects; 20 nurses and 20 patients. Data were collected from May to June 2011 and, for the analysis, we used the methodological reference of the Collective Subject Discourse. Results: The interviews were grouped into two themes: communication between practitioner and patient/family and the importance of the communication process with the family for the patient's recovery. Discussion: The representations obtained were quite similar, especially when considering the difficulties of the communication process, and restricted when reducing it to guidance and information. Conclusion: We confirmed the relevance of communication with family in the recovery of patients.
Keywords: Communication; Nursing; Patients; Family; Emergency medical services